PHARMACOEPIDEMIOLOGY OF ANTIMICROBIAL AGENTS IN NEONATOLOGY: RESULTS OF THE RETROSPECTIVE CROSS-SECTIONAL STUDY - Alexey S. Kolbin; Sergey V. Sidorenko; Yuri V. Lobzin; Dmitry O. Ivanov; Nikolay P. Shabalov; Anton V. Mikhailov; Nikolay N. Klimko; Gennadiy V. Dolgov; Andrey A. Shmidt; Timofey L. Galankin; Alexey A. Kurylev; Elena A. Malikova (Вопросы современной педиатрии)
Background. Infectious diseases remain the leading causes of morbidity and mortality worldwide. Against the background of ever-increasing resistance of bacteria, it is necessary to develop effective measures aimed at the structure optimization of consumption of antimicrobial agents. Therefore, the pharmacoepidemiological data describing either the consumption of antimicrobial agents or the resistance level to them is required. Objective: Our aim was to assess the antimicrobial load in term and preterm newborns during their stay in the maternity wards and/or in the intensive care units (ICU). Methods. A retrospective cross-sectional study has been carried out. The analysis included data of 419 newborns from 5 medical centers. The study has been carried out as part of a multi-purpose program on antibiotic resistance containment being held in St. Petersburg from 2014. Results. The antimicrobial load on the child's body expressed in days of the antimicrobial therapy was 1,838 per 1,000 patient-days in children staying in the ICU for not more than 16 days, and 1,434 per 1,000 patient-days when staying in the ICU for more than 16 days. The average duration of the antimicrobial therapy is 28 days in the ICU and 5 days out the ICU (department for newborns, physiological departments). The most commonly, the children were treated with ampicillin — 384 (92%), gentamicin — 254 (61%), and fluconazole — 150 (36%). The prevalence of off-label prescriptions was 41% (of 1,557 analyzed prescriptions), unlicensed prescriptions — 10%. Congenital infections were the main reasons for prescription of antimicrobial drugs — 225 (62%). Conclusion. The high anti-bacterial load in newborns has been established. The indicator 'days of antimicrobial therapy' in the ICU is 4 times higher than that in the United States. The prevalence of off-label and unlicensed prescriptions is comparable with foreign data.